Idiosyncratic liver pigment alterations of five frog species in response to contrasting land use patterns in the Brazilian Cerrado - Franco-Belussi, Lilian [UNESP]; Provete, Diogo B.; Borges, Rinneu E.; De Oliveira, Classius [UNESP]; Santos, Lia Raquel S. (Peerj Inc, 2020)
Background: Changes in land use trigger environmental changes that can lead to decreased biodiversity and species loss. The liver is an essential detoxification organ that reflects systemic physiological responses to environmental changes. Here, we tested whether contrasting land use patterns influence the amount of substances from the hepatic cellular catabolism and melanomacrophages (MMs) of five anuran species in the Brazilian Cerrado. Methods: We collected the same five species of pond-dwelling frogs in one protected area and in an area with intense agricultural activity. We used routine histological and histochemical techniques to quantify the area occupied by lipofuscin, melanin, and hemosiderin in the liver of two frogs Leptodactylus fuscus, Physalaemus cuvieri, and three tree-frogs Dendropsophus minutus, Scinax fuscomarginatus, and Boana albopunctata. We classified land use types in a buffer around each pond based on satellite images. We then used a double-constrained Correspondence Analysis, a recently developed ecological method to relate functional traits to environmental variables, to test the effect of each land use type on the area of each liver pigment. Results: There was an increase in the amount of melanin in environments with high proportion of agriculture, as well as variation in the amount of lipofuscin and hemosiderin. Liver pigments of P. cuvieri and B. albopunctata varied more strongly in response to land use types, suggesting they could be good indicator species. Therefore, the area of MMs in the liver and the metabolic products in their cytoplasm can be used as biomarkers of environmental changes in regions with intense agricultural activities. Our results add a new perspective to the influence of land use patterns on environmental health by highlighting the effect of environmental changes on internal morphological aspects of animals.
Keywords: Melanomacrophages; Bioindicators; Environmental stressors; Internal pigmentation; Melanin; Liver metabolism